Dosimetric characterization of 3D printed phantoms at different infill percentages for diagnostic X-ray energy range. (July 2020) - Villani, D.; Rodrigues, O.; Campos, L.L.
Abstract: The aim of this paper is to characterize 3D printed phantoms and printing set-ups with different infill percentages for imaging energy X-ray beams attenuation. 3D printing performance was studied using the fused filament fabrication (FFF) technique with PLA (Polylactic Acid) and ABS (Acrylonitrile Butadiene Styrene) filaments. Phantom plates were printed and, using the Pantak Seifert X-ray system with different beam qualities in the diagnostic range, the attenuation coefficients were obtained experimentally with the transmission method and results compared with PMMA used as reference and theoretical data. Different percentages of infill of printed phantoms were also evaluated and transmission characterized. The attenuation coefficients were determined for the different beam qualities and results show that the variation in the values of attenuation coefficients decreases as the infill quality increases. Attenuation characteristics evaluated indicates the suitable equivalence of PLA to PMMA for 3D printing water/tissue equivalent most complex geometry phantoms. The different printing modes characterized together with their attenuation coefficients for the X-ray beams will be studied and used in the development of new 3D printed phantoms in our institute. Highlights: PLA and ABS commercial filaments X-ray attenuation behavior. PLA and ABS X-ray attenuation coefficient for X-ray diagnostic beams. X-ray attenuation for different infill percentages. 3D Printed PLA as suitable substitute for PMMA.